The Influence of Packaging Design on the Performance of Small and Medium-sized Enterprises' Products - Maricar, Rezvanny; Naharuddin, Andi; Rosmiati, Rosmiati (JURNAL ADMINISTRASI KANTOR; Vol 11 No 1 (2023): Jurnal Administrasi Kantor (Juni 2023), 2023)
The purpose of this research is to understand the functions of packaging. It employs two scientific approaches: a broad literature review focused on packaging-related articles and a series of empirical observations of packaging industry cases, with a strong emphasis on packaging. This paper demonstrates its originality by considering the shifting technological opportunities in packaging to ensure a wider range of design choices in packaging, thereby bridging the gap between product packaging and consumers in both digital and conventional marketing. This research is still in its early stages, and the limitations arise from the simple proliferation of smart and interactive packaging in empirical contexts. New packaging technologies and design decisions are expected to have significant practical implications for micro, small, and medium-sized enterprises (MSMEs).   Keywords : Desain packaging, fungsional produk, consumer Experience, tehnologi packaging,